Enhanced Riboflavin Production by Expressing Heterologous Riboflavin Operon from B.cereus ATCC14579 in Bacillus subtilis - 段云霞 陈涛 陈洵 王靖宇 赵学明 (Chinese journal of chemical engineering, 2010)
Fragment containing the whole riboflavin（rib）operons of B.cereus ATCC14579 was detected from GenBank and annotated.The rib operon of ATCC14579 was cloned with Pn,its native promoter,or with P43,the vegetative growth promoter,into the plasmid.Expression analysis showed that heterologous rib operon was operative in B.subtilis.Integrative plasmid with P43-rib fragment was integrated into the chromosome of B.subtilis RH33,yielding transformant B.subtilis PY.With optimized medium components,4.3 g·L -1 of riboflavin was achieved in batch culture of B.subtilis PY,which was 27%enhancement compared to the host strain.Real-time reverse transcription polymerase chain reaction（RT-PCR）analysis indicated that the transcriptional level of ribA maintained 2.8-fold higher with the expression of herterologous rib operon.Furthermore,the stability of B.subtilis PY was increased form 45%to 87%.The high transcriptional level of rib gene and higher stability of B.subtilis PY could explain the increased riboflavin production.